COMPUTER-SUPPORTED COLLABORATIVE WORK BERLANDASKAN TEORI AKTIVITAS, SERTA USAHA MENINGKATKAN COLLABORATIVE AWARENESS - Michael Iskandar (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Computer-supported Cooperative Work (CSCW) is a concept that emphasizes the collaborative aspect in information technology applications. A great many CSCW systems have been developed so that Schill, for example, cites no less than ten different classification foundations. The many choices available can be very confusing for the management of an organization that wishes to implement CSCW.One of the features that must be set up by CSCW software producers is collaboration awareness, which is the ability of the software to